INTERAKSI FILSAFAT ISLAM DAN IRFAN DALAM ḤIKMAH MUTA’ALIYAH - Abolfazl Kiyashemshaki (Sekolah Tinggi Agama Islam Sadra, 2014)
In early period of Islamic thoughts, Philosophy and Irfan were acting as if two opposite poles which are difficult, if not to say impossible, to reconcile. Philosophy more emphasizes on discursive reason as an instrument, while Irfan more believes in intuitive witnessing (mukāsyafah) and puts reason in doubt, to disclose the ultimate reality. However, Muslim philosophers through their deep investigations on both realms tried to end the controversy and to reconcile between them. This spirit has been started by a great philosopher, Suhrawardi, by means of his philosophical thoughts well-known by Illuminationism (Ḥikmah Isyraqiyyah) and found its perfect formulation in the hands of prominent philosopher, Mulla Sadra, with his Ḥikmah Muta’aliyah. This writing tries to adduce some knots of interaction between Islamic Philosophy and Irfan which were formulated by Mulla Sadra in his special and brilliant theories. He succeeded to combine some great thoughts of philosophers and ‘urafā’ in one construction of hikmah, in such a way it can create a harmony which completes each other.